Technological Innovation in the Islamic World: History and Today's Challenges - Yoza, Alifa Putri (Indonesian Journal of Islamic Education and Local Culture, 2024)
In a modern era filled with rapid technological development, the Islamic world faces a number of challenges in technological development. Key factors influencing this advancement are education, economics, and globalization. First, quality education becomes an important foundation in preparing individuals to contribute to technological innovation. However, there are still gaps in access to and quality of education in various Islamic countries. Second, economic challenges include dependence on natural resources and lack of investment in research and development. A greater boost is needed to strengthen the knowledge-based sector of the economy. Third, globalization affects how technology is developed and deployed, while there are still barriers to access and digital infrastructure. International cooperation and investment in internet connectivity are key to overcoming these challenges. By focusing on collaboration, investment, and renewal, the Islamic world can transcend these challenges and become a leader in global technological innovation